The role of public policy in the process of regional convergence - Philippe J. Martin (EIB Papers, 2000)
Spatial concentration of economic activities is one of the most salient features of economic development. The almost parallel urge by policymakers to counteract such a trend through public polices is also striking. This is not only reserved to those countries, especially in Europe, which have a long tradition of public intervention. To a lesser extent, the United States has (for example during the New Deal period) put into place policies aimed at correcting uneven patterns of regional development. Public intervention is usually defended on either efficiency or equity grounds. In the case of economic geography, a justification in terms of efficiency implies identifying the various market failures, specific to the issue of space, that make the optimal economic geography differ from the one induced solely by market forces. Although one also needs to show that public intervention will make a better job than market forces, the identification of market failures is a necessary first step to justify public intervention on efficiency grounds. Whereas this type of analysis has been standard for public intervention in the fields of education, technology, pollution, etc., the counterpart for regional policies is much less developed. There are two ways forward: the first is to analyse how some 'standard' market failures are modified by the introduction of space and distance and how in turn, this should affect the definition of public policies; the second is to understand how space and distance themselves can be at the origin of market failures.
Keywords: 330; Regionalpolitik; Entwicklungskonvergenz; Regionale Disparität; Wirkungsanalyse; Theorie